Effect Of Bioactive Glass on Dentin Hypersensitivity – A Systematic Review - P.Niharika; Iffat Nasim, M.D.S (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Objective: To evaluate whether the dentifrice containing bioactive glass is more effective than dentifrice without bioactive glass in reduction of dentin hypersensitivity . Is there any difference between the dentifrice containing bioactive glass and other dentifrice without bioactive glass in reduction of dentin hypersensitivity. Sources: Five databases were searched to identify the relevant articles published up to December 2020 . Electronic databases were searched in PUBMED , Scopus ,LILACS , Cochrane Library and Google scholar . Two authors had performed the data extraction from the included studies . The primary outcome is to evaluate the response to thermal ,tactile ,cold stimulus for the treatment of dentine hypersensitivity and the secondary outcome is to compare the efficacy of desensitising agents used in the treatment of Dentine hypersensitivity. Each of the included studies was evaluated using the Cochrane Collaboration tool for assessing risk of bias . Study Selection: Randomised controlled trials ( RCTs ) comparing desensitising toothpastes with a toothpaste without the desensitising components . This was evaluated in the patients who suffer from Dentin hypersensitivity were included . The risk of bias was assessed according to Cochrane guidelines using RevMan 5.3 software . Data Collection: A total of 14 RCTs were included in this systematic review . It was clearly stated that the toothpastes that contain active desensitisation ingredients showed a better desensitising effect on Dentin hypersensitivity than that of other groups . Conclusion: According to the 14 (RCT’s) included studies in this systematic review , the bioactive glass containing dentifrice had superior reduction of dentin hypersensitivity compared to dentifrice without bioactive glass .